2013
DOI: 10.1021/ma400738k
|View full text |Cite
|
Sign up to set email alerts
|

Treelike Polymeric Ionic Liquids Grafted onto Graphene Nanosheets

Abstract: Herein we report on a versatile graf ting-to process combined with end group modification to prepare treelike polymeric ionic liquids which are covalently attached to graphene nanosheets. When cationic 3-ethyl-3-hydroxymethyloxetane (EHO) polymerization is initiated in the presence of dispersed hydroxy-functional graphene (FG) nanosheets, chain termination reactions account for highly effective grafting of hyperbranched poly(3-ethyl-3-hydroxymethyloxetane) (PEHO) onto FG. Tosylated PEHO hydroxy end groups are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 58 publications
1
23
0
1
Order By: Relevance
“…204 Such ionic liquid nanoreactors can be used to perform chemical reactions in confined, isolated, and restricted ionic liquid geometries. 40 The interesting properties of POSS-containing oligo(ionic liquid)s such as their low melting temperature and high ion conductivity enable the use of these ionic materials as electrolytes in various electrochemical devices such as solar and fuel cells 155 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 liquids with low vapor pressure show ion conductivity with the IL component acting as a plasticizer for the polymeric membrane and assisting the charge transport ( Figure 19a). 191 Generally, for fuel cell applications, it is necessary to achieve high proton transference.…”
Section: Emerging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…204 Such ionic liquid nanoreactors can be used to perform chemical reactions in confined, isolated, and restricted ionic liquid geometries. 40 The interesting properties of POSS-containing oligo(ionic liquid)s such as their low melting temperature and high ion conductivity enable the use of these ionic materials as electrolytes in various electrochemical devices such as solar and fuel cells 155 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 liquids with low vapor pressure show ion conductivity with the IL component acting as a plasticizer for the polymeric membrane and assisting the charge transport ( Figure 19a). 191 Generally, for fuel cell applications, it is necessary to achieve high proton transference.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Although at this point there is no universally accepted definition of "poly(ionic liquid)s", they are usually regarded as macromolecules containing ionic groups that are characteristic of classical ionic liquids (so-called "ionic liquid groups", "ionic-liquid functionalities", or "imidazolium-type ionic" compounds). 38,39,40 Oligomers occupy the intermediate molecular weight range between monomers and polymers and are regarded as a unique class of compounds composed of linked repeat units. 41 To this end, oligo(ionic liquid)s (OILs) with molecular weights below 10 kg/mol have traits of both ionic liquids and poly(ionic liquid)s. Unlike poly(ionic liquid)s, many oligo(ionic liquid)s are still able to preserve a liquid aggregate state in a broad range of temperatures, are often water-soluble, and have a strong dependence of properties on the number and type of ionic end groups and constitutional units.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can stabilize the dispersion electrostatically thus preventing the agglomeration of graphene nanosheets 18a. 19d Additionally, CNT‐Ima also shows a good dispersibility behavior in different solvents, but agglomeration started already after 3 h (Supporting Information, Figure S4). This behavior can be due to advantages of CRGO over CNT such as high surface area, and less tendency to tangle, as discussed earlier 28…”
Section: Resultsmentioning
confidence: 99%
“…Hyperbranched (hb) polyoxetanes, which are commonly obtained by the cationic ring‐opening polymerization (CROP) of oxetanes with a pendent hydroxyl group (latent AB 2 monomers), have attracted increasing attention in recent years . In contrast to their linear homologs, hb polymers show lower viscosity, improved solubility and almost no entanglements because of the compact structure and multivalency .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported molecular weights of PEHO up to 9400 g mol −1 and Xia et al PDIs of poly(3‐methyl‐3‐hydroxymethyl)oxetane around 1.2 via CROP . The DB varied around 50% and seemed to depend on the reaction temperature in a lower temperature range (−50 to 30 °C) . Schulte et al reported that during polymerizations to linear products self‐initiation of oxetanes can lead to cyclic byproducts, which impedes a controlled CROP .…”
Section: Introductionmentioning
confidence: 99%